Composition and dynamics of bladder, vaginal and bowel microbiota during three trimesters in healthy pregnant women - Yu. L. Naboka; N. V. Vorobyeva; I. A. Gudima; T. G. Sinyavskaya; R. S. Ismailov; K. G. Naber; M. I. Kogan (Вестник урологии)
Introduction. The microbiota dynamics of the core biotopes during pregnancy are hardly studied, although changes in these compartments have an important role in both the functioning of the female organism and foetal development.Objective. To study the dynamics and interactions of changes in bladder, vaginal and bowel microbiota in healthy pregnant women over three trimesters (TRI-1, 2, 3).Materials & Methods. Study design: a single-centre comparative observational longitudinal study. Thirty out of first-time 220 pregnant women were selected for screening at the antenatal clinic from 2021 to 2022. All pregnant women underwent sampling at T-1, 2, 3: mid-stream bladder urine samples, posterior vaginal swabs and faecal masses were collected for culture study. After a special pre-culture preparation, samples were examined on an expanded set of nutrient media (n = 13) using special cultivation (aerobic-anaerobic) conditions. Based on the research results, identification frequencies (IDFs), microbial load values (MLVs) and microbial co-occurrence coefficients between the different biotopes were estimated.Results. Culture study revealed various bacteria in each biotope investigated during all TRIs. In the urine, aerobes and anaerobes were observed from TRI-1 to TRI-3 with different IDFs, but no taxa showed a stable IDFs. In the vagina, IDFs of bacteria were similar to urinary. The bowel microbiota was the most stable biotope remained almost unchanged during pregnancy. In the urine and vagina, mean MLVs of most aerobes and anaerobes did not change significantly throughout pregnancy. In the bowel, MLVs were consistently higher than in the urine and vaginal swabs. According to the co-occurrence analysis bladder-vagina and bladder-bowel biotopes showed significantly more interconnections between microorganisms in all TRIs.Conclusion. The observed microbiota structure during all TRIs is associated with uncomplicated gestation. These results will be valuable for studying changes of microbiota in complicated pregnancies.